ps-TRIR investigations of DNA systems and toward bimodal nanoparticles for biomedical applications - Doorley, Gerard W. (Trinity College (Dublin, Ireland). School of Chemistry, 2009)
The work described herein encompasses two distinct areas of chemistry. The first of these involved the time resolved study of ultrafast relaxation processes in DNA following UV excitation (chapters 1-5). The nature of the electronic excited states of DNA is today an ever expanding area of scientific curiosity. Exposure of DNA to UV radiation can result in deleterious effects with profound biological consequences. Our goal is to understand the excited states formed and their subsequent reaction or relaxation dynamics. To this end, we have embarked on a systematic study from simple nucleotide units to dinucleotide, polynucleotide and finally biologically relevant systems using picosecond time resolved infrared spectroscopy (ps-TRIR).
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin